A Model to Estimate the Level of Passenger Satisfaction With the High-Speed Train - Prayudi; Mulyono, Agus Taufik; Najid; Sari, Endah Murtiana (Civil Engineering Journal, 2025)
Passenger satisfaction must be measured by operators providing high-speed train services, as it is directly related to passenger loyalty, which in turn ensures the business's sustainability. This study aims to measure passenger satisfaction with the Jakarta-Bandung high-speed train by developing a model that considers various factors significant in influencing user satisfaction. The quantitative method was developed by distributing questionnaires to 300 respondents, and the results were analyzed using SEM. The results of this study prove the existence of a model built from 5 (five) dimensions: the availability of information, accessibility, train comfort, emergency actions, and responses to complaints. The results of this study are expected to provide recommendations to the operator of the Jakarta-Bandung High Speed Train to evaluate the factors of 5 (five) dimensions that are considered important in forming a user satisfaction model for the service using a performance analysis matrix (IPA Diagram). According to the results of the IPA diagram, it is evident that the most urgent task for the operator is to consolidate with third parties related to the availability of modes to serve passengers who will continue their journey to Bandung, particularly for work and tourism purposes.